Using CLV concept for marketing budgets allocation - Olga K. Oyner; Olga Sukhorukove (jbm - Journal of Business Market Management, 2013)
The paper evaluates the usefulness of customer lifetime value (CLV) as a metric for marketing budget allocation by developing a framework that enables managers to maintain customer relationships proactively through different elements of marketing mix, in order to maximize CLV. The analysis is based on data from a hardware components PC B2B company and suggests that there is a potential for increased sales and CLVs when managers design resource allocation rules that maximize CLV. Managers can use the authors' framework to distribute marketing resources efficiently across customers and when choosing between different promotional activities.
urn:nbn:de:0114-jbm-v6i2.364
Keywords: 650; marketing performance; customer lifetime value; marketing budgets; resources allocation